PENGARUH MOTIVASI, STATUS EKONOMI, INFORMASI PERGURUAN TINGGI TERHADAP MINAT S2 MELALUI PRESTASI - Aini Aziza; Yon Rizal; Albet Maydiantoro (FKIP Unila, 2019)
The purpose of this study was to determine the effect of learning motivation, socio-economic status of parents and college information on the interest of continuing studies S2 through student learning achievement in Economics Education 2015 FKIP force Lampung University academic year 2018/2019. The method used is descriptive verification with ex post facto approach and survey. The population in this study were students of Economic Education in 2015 FKIP force Lampung University totaling 84 students with the amount of sample was 69 students. The sampling technique used is the probability sampling with simple random sampling. The results showed that there was a significant effect of learning motivation, parents' socio-economic status and college information on the interest in continuing S2 studies through learning achievement in 2015 class of Economics Education students at the Teacher Training and Education Faculty of Lampung University academic year 2018/2019 by 55% Tujuan dari penelitian ini adalah untuk mengetahui pengaruh motivasi belajar, status sosial ekonomi orang tua dan informasi perguruan tinggi terhadap minat melanjutkan studi S2 melalui prestasi belajar pada mahasiswa Pendidikan Ekonomi angkatan 2015 FKIP Universitas Lampung tahun akademik 2018/2019. Metode yang digunakan adalah deskriptif verifikatif dengan pendekatan ex post facto and survey. Populasi dalam penelitian ini adalah mahasiswa Pendidikan Ekonomi angkatan 2015 FKIP Universitas Lampung yang berjumlah 84 mahasiswa dengan jumlah sampel berjumlah 69 mahasiswa. Teknik pengambilan sampel yang digunakan yaitu probability sampling dengan simple random sampling. Hasil penelitian menunjukkan bahwa ada pengaruh yang signifikan motivasi belajar, status sosial ekonomi orang tua dan informasi perguruan tinggi terhadap minat melanjutkan studi S2 melalui prestasi belajar pada mahasiswa Pendidikan Ekonomi angkatan 2015 FKIP Universitas Lampung tahun akademik 2018/2019 sebesar 55%.Kata kunci : motivasi, status, informasi, prestasi, minat